Measurement of lumbar spine bone mineral: a comparison of dual photon absorptiometry and computed tomography. - Sambrook, P; Bartlett, C; Evans, R; Hesp, R; Katz, D; Reeve, J (1985)
A comparison of computed tomography (CT) and dual photon absorptiometry (DPA) in the measurement of spinal bone mineral was made in 44 subjects of whom 26 had vertebral crush fractures. Although CT measures only trabecular bone within the vertebral body whilst DPA measures the whole vertebral segment, a good correlation was observed (r = 0.80) when these quantities were expressed in dimensionally similar units. Trabecular bone in the distal radius measured by CT correlated less well with vertebral CT (r = 0.65). Cortical bone in the radius correlated poorly with the spinal DPA measurement (r = 0.38).